Pengaruh Relationship Marketing dan Kualitas Produk terhadap Kepuasan Pelanggan pada Catering Kencana Lampung Selatan - Putra, Olyvinanda Diaz; Suhaimi; Suradi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2023)
Catering is a business engaged in food services, this business serves food for weddings and other parties on a large and small scale, with the development of culinary business activities in Lampung, catering is one of the businesses thatbenefit for now, therefore this business requires Relationship marketing to build long-term relationships with customers. This study aims to determine the effect of Relationship marketing and product quality on customer satisfaction in South Lampung Kencana Catering, This type of research is quantitative research. The data collection instrument uses the distribution of questionnaires to Catering Kencana customers. The population in this study is all Kencana Catering customers in 2022, the research sample used in this study amounted to 44 people using the saturated sample technique. Testing is carried out by Multiple Regression by testing classical assumptions first, then testing the hypothesis partially with Test t and simultaneously with Test f. then looking for the coefficient of determination to see how much the percentage of variance of the independent variable affects the dependent variable. The results stated that partially and simultaneously the two independent variables studied, namely Relationship marketing and product quality, had a positive and significant effect on customer satisfaction with a fairly large coefficient of determination value of 74.5% and the rest was influenced by other variables that were not studied in this study. Keywords: customer satisfaction, product quality, relationship marketing